Tall buildings : sixth International Conference on Tall Buildings ; Mini Sympoisum on Sustainable Cities ; Mini Symposium on Planning, Design and Socio-Economic Aspects of Tall Residential Living Environment, Hong Kong, China, 6-8 December 2005 - Cheung, Y. K.; Chau, K. W. (Kwong Wing) (World Scientific, 2005)
A collection of papers presented at the Sixth International Conference on Tall Buildings (ICTB), this volume clearly explains the engineering and socio-economic aspects of tall buildings in specific areas of sustainability. The papers focus on Asian cities, where tall buildings have become a major feature of the built environment. A multi-disciplinary book, it also deals with the increasing complexity of inter-related problems that require knowledge integration from different disciplines. With interesting contributions from distinguished practitioners, academics and policy makers, the book addresses the development and application of knowledge in solving problems related to tall buildings.